Electrochemical performance and durability of flat-tube solid oxide electrolysis cells for H2O/CO2 co-electrolysis. (28th February 2022) - Xi, Chengqiao; Sang, Junkang; Wu, Anqi; Yang, Jun; Qi, Xiaopeng; Guan, Wanbing; Wang, Jianxin; Singhal, Subhash C.
Abstract: Co-electrolysis of H2 O and CO2 by high-temperature solid oxide electrolysis cells (SOECs) is a useful approach for energy storage and carbon dioxide reduction. In this study, we conducted H2 O/CO2 co-electrolysis using a flat-tube SOEC and studied its electrochemical performance and durability. It was found that the increase of temperature and water fraction in fuel gas promote electrochemical performance. In addition, the co-electrolysis was found to be stable with a constant current density of 300 mA cm −2 for over 1000 h at 750 °C. The contribution of each electrode process to polarization resistance is elucidated by electrochemical impedance spectroscopy and distribution of relaxation time (DRT) analysis. The fuel electrode was found to degrade more significantly against duration time as compared to the oxygen electrode. Post-mortem analysis of the microstructure revealed the loss and sintering of Ni particles in active cathode functional layer at the inlet of the fuel electrode. Based on these results, the degradation mechanism of H2 O/CO2 co-electrolysis by the flat-tube SOEC was discussed in details. Highlights: H2 O/CO2 co-electrolysis was successfully conducted by using a flat-tube (FT) SOEC. Performance of the FT cell for co-electrolysis was studied by EIS and DRT methods. 1000 h of co-electrolysis has been carried under a current density of 300 mA cm −2 . The loss and agglomeration of Ni are the important causes of cathode degradation.